Analisis dan Perancangan Sistem Informasi Permintaan Pengadaan Perangkat dan Layanan IT (Studi pada Departemen IT PT Eratex Djaja Tbk Probolinggo) - Hetty Mukammilah; Yusi Tyroni Mursityo; Nanang Yudi Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
PT Eratex Djaja Tbk is a garment factory that located in Probolinggo. The main operation for the factory is apparel manufacturing and finishing. IT department is an unit that provides tech support services such as configuration, utilization, dan problem solving concerning IT problems in the factory. The Applicant of the request for IT services must fil out a request form that provided by IT Department before IT Department could carry out the service request. Periodically, IT Department must go through the request forms one by one in order to make summary report of their work of a certain period of time. That work requires a long time and there is also risk of missing the request form before being archived. Based on the problems mentioned, this study conducted information system analysis dan design on web-based service request form and management of request of IT service. Rational Unified Process (RUP) used as a method to carry out the system design process. The system design process was conducted using the Object-Oriented Analysis and Design (OOAD) approach and Unified Modeling Language (UML). The system design that have been built evaluated using Requirement Consistency Analysis (RCA) and Cognitive Walkthrough (CW) evaluation method. The RCA evaluation result shows that the assessment results is 100% which means the relation of the design and all elements of the system requirement from the four layers frameworks have been consistent. The result of CW evaluation performed by the Supervisor and the Staff of IT Department shows that all the features of the system is fully in line with their expectations.